Estudo da capacidade funcional, função pulmonar, força e endurance muscular respiratória em mulheres obesas, comparadas com os valores preditos - Alves, Viviane Cristina (2018)
Introduction: Obesity is characterized by excessive accumulation of body fat bringing prejudice to the health of the individual, presents several associated morbidities among them respiratory changes and functional capacity, interfering with ability physics of the obese individual. The lack of scientific evidence on these aspects justify the need for studies that seek to explore the changes in respiratory muscle strength and endurance and the relation that these variables feature with the degree of physical performance in individuals obese. Objectives: to evaluate the maximum inspiratory pressures (MIP) in obese women, obtained by manovacuômetro (MIPMV) and by the RT2 (MIPRT), in addition to respiratory muscle endurance (RME) obtained from RT2 represented by the Maximum inspiratory pressure Sustained (SMIP) and the maximum voluntary ventilation (MVV) obtained by spirometry and functional capacity by Incremental Shuttle Walk Test (ISWT) and compare the findings with predicted values equations found literature. Methods: this was a cross-sectional study, including 103 obese women aged between 18 and 65 years and body mass index (BMI) between 30 and 60 kg/m2, in which the values were measured spirometry (FVC, FEV1/FVC and FEV1), in addition to the MIPMV and MIPRT , SMIP and Incremental Shuttle Walk Test (ISWT). Results: the results showed that the obese MIPMV of 98 ± 24.3 presented cmH2O, bigger than MIPRT 74.2 ± 29 cmH2O and, when compared with the equations of predictive values for individuals were less than eutrophic and showed correlations negative with the IMC. The values obtained from MVV and SMIP were compared to their predicted, were reduced only for the MVV being obtained 90% of predicted. For the ISWT the values obtained (334 ± 80 m) were reduced to 60% of predicted (554 ± 72metros) with p < 0.001. Conclusion: obesity has negative direct relationship on the RMS and RME, PME. The higher the degree of obesity greater influence over these variables.